Exploring pre-service mathematics teachers’ knowledge of content and students through case reading and discussion - Nadide Yılmaz (Journal of Pedagogical Research, 2022)
The importance of case reading and discussion has been steadily increasing in teacher education. This study attempted to investigate what changes, if any, have been brought about by pre-service mathematics teachers’ working on cases on their knowledge of content and students. Nineteen pre-service teachers participated in a 14-week teacher training program and worked on cases related to concepts in the learning area of numbers. The current study employed the mixed method and used the written records constituted by the cases on which the pre-service teachers worked on and the audio recordings of the discussion processes as the data collection tools. In the analysis of the collected data, content analysis was used. The findings revealed that the pre-service teachers’ working on cases contributed to the development of their knowledge of content and students. The pre-service teachers were able to comment more on how students think and where they can have difficulties and understand the reasons behind these difficulties in the later stages of the training. The findings also revealed that the cases the pre-service teachers were engaged in helped them feel like a real teacher. The results showed that case reading and discussion can be one of the important contributors to the development of the pre-service teachers’ knowledge of content and students.